Creating Spaces for Arts-Informed Responses in Teacher Education Programs (LEARNing Landscapes, 2016)
We address the bene ts and challenges of using an arts-informed response in an undergraduate teacher education course from the perspective of a teacher and two students. Feminist pedagogies provide the theoretical lens through which our experiences are analyzed. From the teacher’s perspective, this arts-informed approach modeled to pre-service teachers how they could use arts-informed inquiry in their future classrooms, to engage in conscious raising about inequality, while meeting di erent learning styles in their classrooms. From the students’ perspective, it was surprising to be invited to do an arts-informed reading response. Acceptance depended on the perception of risk. Our conclusion is that more space should be created for arts-informed approaches in undergraduate teacher education programs.
Keywords: arts-informed; teacher education; feminist pedagogy; undergraduate